ANALYSIS OF STUDENTS’ MATHEMATICAL LITERACY SKILL IN SOLVING PISA MATHEMATICAL PROBLEMS - Yusfa Lestari; Abdur Rahman As’ari; Makbul Muksar (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to determine students’ mathematical literacy skills in solving PISA mathematical problems. Mathematical literacy is the capacity of individuals to formulate, use, and interpret mathematics in various contexts. Students’ mathematical literacy skills can be seen in the way students work in solving PISA questions. This study is qualitative descriptive research. Data from the analysis of students’ mathematical literacy skills were obtained through tests in the form of descriptive questions adopted from PISA questions, analysis based on indicators of mathematical literacy skill according to PISA, and the interview results with students who worked on the PISA questions. This study shows that students’ mathematical literacy skills were in the medium to the low category; this can be seen from the percentage of students’ answer scores in working on PISA questions. Therefore, it is necessary to provide reasoning questions such as PISA questions to help students improve their mathematical literacy skills.